Spatial Management Units as an Ecosystem-Based Approach for Managing Bottom-Towed Fisheries in the Central Mediterranean Sea - Lauria, Valentina; Gristina, Michele; Fiorentino, Fabio; Attrill, Martin J.; Garofalo, Germana (Frontiers in Marine Science, 2020)
Marine ecosystems are being continually impacted by human activities and, among these, fisheries have been one of the most damaging. Fisheries modify the structure and functioning of food-webs through biomass removal and physical damage to the seabed, leading to loss of biodiversity and ecosystem services provided by the oceans. The ecosystem-based approach to fisheries is considered the most efficient way to achieve the goal of sustainable use of marine resources while allowing for biodiversity protection. The Strait of Sicily is a biologically important area of the central Mediterranean Sea characterised by high habitat complexity and rich biodiversity; however, due to the multispecific nature of local fisheries and weak implementation of the adopted management plans, this region is particularly vulnerable. We used fishery independent time series (1994-2016) to identify the main demersal assemblages and map their spatial distribution. The pressure of fishing effort on each of these defined assemblages was then quantified in order to evaluate the impact of bottom trawling on demersal communities. Our results showed four spatially distinct and temporally stable assemblages of the Strait of Sicily. These have a clear spatial distribution, different species composition and biodiversity values and are driven primarily by environmental gradients (i.e. mainly depth and, to a lesser extent, surface salinity). The demersal assemblages were subsequently grouped in homogeneous areas characterised by specific communities of commercial and non-commercial species and response to trawling impacts. These areas are proposed as Spatial Managements Units to evaluate and manage demersal mixed fisheries, while also considering biodiversity conservation in the central Mediterranean Sea.